2004
DOI: 10.1111/j.1530-7085.2004.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Pain—Part 1: Etiology, Epidemiology, and Prevention

Abstract: Work-related musculoskeletal disorders (MSDs) have reached a costly epidemic proportion in recent years, producing ergonomic pain as their most frequent clinical consequence. While work-related MSDs have declined in incidence, their prevalence continues. Individuals develop symptoms as a consequence of numerous factors that include force, sustained posture, repetitive motion, and vibration. Different combinations of these factors lend to different pathomechanical and pathophysiological consequences that appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 50 publications
1
19
0
4
Order By: Relevance
“…As the correlations among the variables, the fact of it being found signifi cant correlation between the categorized postures deviations and the impact in the ankle in the axis z (latero-lateral) and between the lesions and the impact in the ankle in the axis y (vertical), are information in the literature that ratify the information of Sizer et al 24 , when they affi rm that great part of the postures alterations in athletes is due to the characteristic of the motor gestures and in the way as the training is done, as well as, Santos et al 3 that considering the measured magnitudes of impacts in the landings of the cut in volleyball athletes and if using of analytical calculations simulated that an athlete in landing after a cut , have a corporal mass of 60 Kg, with variation of the vertical displacement of the center of 0,4m mass, with a speed of 2.8 m.s -1 , he will be submitting his ankle to an impact force of approximately of 1784.37N.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…As the correlations among the variables, the fact of it being found signifi cant correlation between the categorized postures deviations and the impact in the ankle in the axis z (latero-lateral) and between the lesions and the impact in the ankle in the axis y (vertical), are information in the literature that ratify the information of Sizer et al 24 , when they affi rm that great part of the postures alterations in athletes is due to the characteristic of the motor gestures and in the way as the training is done, as well as, Santos et al 3 that considering the measured magnitudes of impacts in the landings of the cut in volleyball athletes and if using of analytical calculations simulated that an athlete in landing after a cut , have a corporal mass of 60 Kg, with variation of the vertical displacement of the center of 0,4m mass, with a speed of 2.8 m.s -1 , he will be submitting his ankle to an impact force of approximately of 1784.37N.…”
supporting
confidence: 72%
“…Although, according to Sizer et al 24 , great part of the postures alterations is due to the characteristic of the motor gestures and in the way as the training is done, since mechanical and physiologic alterations are directly related with the activity that the individual performed, it seems that for the participants of this study this fact is not still visible.…”
mentioning
confidence: 91%
“…This finding of variation between the lumbar disc injuries warrants further investigation considering the high costs of lumbar disc claims and that there may be unique risk factors specific to individual industries. Previous research indicates lumbar disc injuries are associated with job demands of bending, twisting, and heavy lifting [Sizer et al, 2004]. The average cost per claim of lumbar disc found in this study ($52,041) compares with the State of Washington ($46,553) [Silverstein, 2002].…”
Section: Discussionmentioning
confidence: 68%
“…However, mean age among our CTS claimants was 42.8 whereas Silverstein's was 37.0 years old [Silverstein, 2002]. Although the incidence of CTS has reportedly declined, the condition is still commonly associated with work-related factors and demands [Sizer et al, 2004;Osorio et al, 1994] that are commonly found in the service and manufacturing industries [Kao, 2003].…”
Section: Discussionmentioning
confidence: 90%
“…Work‐related musculoskeletal disorders (MSDs) have reached a costly epidemic proportion in recent years, producing ergonomic pain as their most frequent clinical consequence 1 . While work‐related MSDs have declined in incidence, their prevalence continues.…”
Section: Introductionmentioning
confidence: 99%